A Liquid Episteme: Roberto Bolaño, Fictional Biographies, and the Enlightenment. - Estrada, Jorge Ismael; Yurgel, Caio (Hispanic Review)
The lives that inhabit Roberto Bolaño's fiction serve as a contestation to the tenets of the Enlightenment. In this respect, water plays a key role in the author's poetics: a metaphor for defeat and madness which both reflects and muddies the horrors of Reason. By examining Bolaño's ability to create complex fictional biographies, this article identifies how these characters' encounters with watery metaphors reveal the depths of Bolaño's critique of the Enlightenment belief in an all-knowing and all-seeing Reason. To achieve our goal, we explore the lives of characters from four of his novels: 2666 , Monsieur Pain , Amulet , and By Night in Chile. This article demonstrates how Bolaño conceives characters who are asked to take a stand in a world of diminishing certainties and changing tides. In doing so, he superimposes characters with minimal variations on the same backdrop of an ethically compromised world, like a scientist trying to pinpoint the exact moment that got us to where we now are.